Synergistic effect of transport services compatible to loads - Andrii Galkin (Cхід, 2013)
The result of the integration process may be a synergistic effect, if the possibility of increasing the efficiency of the logistics system by strengthening mutual ties of a logistic system and supply chain to another or from the environment at the input and output of material and information flows .The issues of supply chain integration and synergy. The questions at synergetic effect in compatible cargo transport services. Author simulate the process of traffic compatible cargo, provided that a carrier vehicle will serve several joint loads, these can reduce downtime due to rational distribution of orders between cars. As a result, the survey found that the frequency and volume of traffic at different times vary and depend on seasonal consumption, day of the week. Therefore, the work is dedicated vehicle that is simple track. Analysis of scheduling vehicles serving three logistics system, showed that the redistribution of orders between vehicle due to different rotation lengths in different systems, serviced, led to a reduction in the number of track. Thus, consider the synergistic effect of transported cargo joint that served a carrier, such as a possible reduction of the required number of vehicle to serve the needs of customers through the redistribution of the carrier vehicle. The method for determining the number of trips that can make a vehicle with a complex servicing several joint loads.